THE NARRATIVE AS THE STRATEGY AND PRACTICE OF POSTMODERN RENEWAL OF SOCIAL AND HUMANITARIAN KNOWLEDGE METHODOLOGY - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The peculiarity of postmodern conception “narrative” and its consequences for spreading in social and humanitarian knowledge is observed.